(untitled) (Raparin Journal of Humanities (RJH), 2024)
Gender identity refers to the way humans view themselves and perceive themselves to be attractive both sexually and romantically. It is an individual’s appreciation and satisfaction of being heterosexual, bisexual, homosexual, or cisgender. It refers to an individual’s sexual understanding of himself and is part of one’s identity, which is different from the sexual understanding of oneself. Gender identity disorder means a robust desire of pertinence towards the opposite sex and robustly insistence on this otherness. Avoidance is classified within the framework of cluster 3 of personality disorders, which is identified by The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Hence, one can argue those who have this kind of personality disorder may appear in them withdrawal behavior; and they view themselves as restless, and they feel that they are rejected and despised by others. The researcher argues that homosexuals in Kurdish society are not accepted, and a large majority of people see them as sick, and others as victim due to their vulnerability to social and psychological problems. This study aims at finding relations between gender identity disorder and symptoms of avoidance in homosexual persons. The descriptive and relational methodology is used to intentionally select 108 subjects, 84 males and 24 females. Based on literatures and contemporary studies in the field, the researcher prepares the items of the gender identity disorder, yet for symptoms of avoidance, the researcher relies on and takes its terminologies from The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). The terminologies in both variables are presented to groups of experts in education, psychology, and psychiatrics, and for extracting stability from both the measures, (split-half) and (alpha Cronbach’s) is used. After applying the last measures on individuals from the sample of the study, statistics of the data is analyzed using Statistical Package for the Social Sciences (SPSS). The study concludes that there is a robust, positive and significant correlation between gender identity disorder and avoidance symptoms among homosexuals. Based on the results recommendations are also given.